asuhan keperawatan jiwa pada tn.e dengan gangguan isolasi sosial : menarik diri di ruang arjuna rsjd surakarta - baharudin ridlo, han; , Sahuri Teguh, S.Kep., Ns (2015)
Background : WHO estimate the as many 450 million people worldwide experience a mental disorder, 26 million of which the population of Indonesia. Social isolation is a disorder of interpersonal relationships. Humans as social beings who can not live individually and must interact with other individuals to make ends meet. Purpose : To provide nursing care to clients with impaired social isolation: withdrawal in Room Arjuna Mental Hospital of Surakarta with methods that include assessment, data analysis, formulation problems, nursing interventions, implementation and evaluation of nursing. Results : After nursing care actions with strategy implementation methods 1 to 3 for 3x24 hours showed that the client is able to determine the cause of social isolation, advantages relate to others and losses not related to the others, how to get acquainted with the nurse, how to get acquainted with other nurses and how to get acquainted with other clients. For a process that is not achieved is the implementation strategy for the family because the family did not come to visit a client. Conclusion : The harmony between families and medical personnel with the data obtained by the action given to the client is very influential on the success of nursing care to clients with impaired social isolation withdraw. Keywords : social isolalsi disorders, withdrew.